The SISTEM PERINGATAN KEBAKARAN PADA MOBIL BERBASIS IOT: - Muhammad Azhar Robbani Azhar; Yudan Aloya Pagalo (Universitas Widyatama, 2022)
Fire is an event of uncontrolled fire that can endanger the safety of human life and can harm property. Based on BPS data in 2020 for the DKI Jakarta area, it contributed quite a lot of fire events. In residential areas, 1898 houses were burned, in public buildings around 429 units were burned, in industrial buildings around 17 units were burned, and motor vehicles accounted for 137 vehicles burned. ESP32 is a microcontroller equipped with an integrated wifi module and Bluetooth low energy (BLE), this ESP32 functions to process data from sensors that are converted into temperature units and as an indication of the presence or absence of fire. Data from the microcontroller is sent via a wifi network to the Telegram BOT server, the average speed of data transmission between the microcontroller and the server is 3.33 s.